Tourism / A New Perspective - Burns Peter; Holden Andrew (Prentice Hall, 1995)
This book sets out to introduce the subject of tourism, challenge conventional wisdom about it and address its ''problematique'', particularly how tourism integrates within a global system of development and impact. Introduction, Supply and Demand: The Commoditization of Tourism, Motivation and Tourists' Perspectives and Marketing, Globalization and the North-South Debate and Tourism Employment, Commodities and Culture and the Division of Labor, Economic Impacts of Tourism, Progress: From Rice Paddy to Golf Green - Environmental Issues and Tourism, Planning: Retrospection and Interventions and Approaches, Alternative and Sustainable Tourism Development - The Way Forward?, References, Index.